HDL: To treat or not to treat? - Pirillo, A.; Tibolla, G.; Norata, Giuseppe; Catapano, A. (2014)
Several studies have shown an inverse relationship between HDL cholesterol (HDL-C) levels and the risk of cardiovascular disease. Low HDL-C levels are commonly present in subjects with diabetes, metabolic syndrome, or obesity. These observations have suggested that increasing HDL concentrations might help in decreasing the cardiovascular disease risk. However, despite initial positive results, some recent data from clinical trials with HDL-raising therapies failed to confirm this hypothesis; in addition, data from Mendelian randomization analyses showed that nucleotide polymorphisms associated with increased HDL-C levels did not decrease the risk of myocardial infarction, further challenging the concept that higher HDL-C levels will automatically translate into lower cardiovascular disease risk. Differences in the quality and distribution of HDL particles might partly explain these findings, and in agreement with this hypothesis, some observations have suggested that HDL subpopulation levels may be better predictors of cardiovascular disease than simple HDL-C levels. Thus, it is expected that increased HDL-C levels may be beneficial when associated with an improvement in HDL function, suggesting that pharmacological approaches able to correct or increase HDL functions might produce more reliable clinical benefits. © 2014 Springer Science+Business Media.